Hate Speech, Impolite Expressions and the Malay Wisdom (Jurnal Bahasa, 2025)
The term "hate speech" is closely associated with social media. Any utterances disseminated with the intent to incite, promote, or justify hatred between races, xenophobia, or anything containing hateful expressions is categorised as hate speech. Hate speech can cause harm to individuals and society. Research on hate speech still limited and has room for exploration. This study aims to examine whether social media posts in Malaysia reach the level of hate speech or remain merely as impolite expressions. Furthermore, the researcher explores the relationship between such expressions and the Malay concept of akal budi (wisdom and moral sense). Data were collected from Instagram users over a three-month period. Analysis was based on Relevance theory, specifically Cross-Referencing Framework (RRS), followed by contextual information highlighting the seriousness of hate speech. Words and phrases such as "walaun", "madanon", and "type C" are often used. While not overtly hateful, these terms do carry hateful connotations upon closer analysis, but their severity leans more toward impolite speech. These utterances were then mapped onto metaphors related to the senses of mouth and ear. For example, "talk too much" and "in one ear and out the other" illustrate the harm of hate speech if left unchecked. This study open avenues for further research on human communication on social media and its relation to the Malay mind. It also demonstrates that the link between hate speech and the senses has long existed and remain relevant today.Keywords: Hate speech, metaphor, social media, impolite speech, Instagram, Malay moral philosophyFull text: PDF